Development and feeding behavior of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) on different sunflower genotypes under laboratory conditions - Truzi, Caio Cesar [UNESP]; Vieira, Natalia Fernanda [UNESP]; Laurentis, Valeria Lucas de [UNESP]; Vacari, Alessandra Marieli [UNESP]; De Bortoli, Sergio Antonio [UNESP] (Springer, 2017)
The aim of this study was to assess the biological aspects and food preferences of Helicoverpa armigera fed different sunflower genotypes and an artificial diet. Tests were performed under multiple-choice and no-choice conditions to evaluate the biological characteristics of H. armigera. In addition, the biological data obtained were used to determine parameters of fertility life tables. The results showed that H. armigera does not have a feeding preference among the sunflower genotypes tested. The larval period on sunflower ranged from 15.0 to 16.2 days. The maximum fecundity on sunflower was 542.6 eggs/female and that on the artificial diet was 794.5 eggs/female. In general, insects feeding on Helio 250 consumed greater quantities of leaves, had higher survival until the end of the pupal stage, displayed high population growth rates, and had low population doubling times, suggesting that in the field populations will achieve greater population densities when fed on Helio 250. Insects that fed on CF101 consumed smaller leaf areas, had lower survival until the end of the pupal stage, lower fertility rates, and lower population growth rates, and may also have displayed lower population densities and smaller reductions in field productivity. This insect developed best on an artificial diet in comparison to sunflower genotypes studied.
Keywords: Insect biology; Helianthus annuus; Integrated pest management